Síntese e caracterização de um complexo de Cu(II) com derivado sulfurado de fenantrolina. Estudos de interação com DNA e adsorção sobre ouro - Cabral, Gabriel Alencar Julião (2023)
Coordination compounds began to be studied in chemotherapy at the end of the 1960s after the discovery of the antitumor activity of the cis-[PtCl2(NH3)2] complex, called cisplatin. The side effects caused by platinum-based metallopharmaceuticals, however, motivated the study of new complexes using different metal centers. In this sense, copper complexes containing aromatic ligands have been widely studied for associating the production of reactive oxygen species (ROS) with the ability of ligands to intercalate with DNA, making possible DNA cleavage and, consequently, cell death. Inserted in this context, the objective of this work was to synthesize and characterize a Schiff base with intercalating properties, the compound (E)-N-(4-(methylthio)phenyl)-1-(1,10-phenanthrolin-5-yl) metanimine (phen-Bz-Sme), and the complex [Cu(phen-Bz-Sme)2(NO3)](NO3), in addition to studying the interaction of the complex with DNA and its ability to generate ROS. The unprecedented molecule fen-Bz-Sme was characterized by nuclear magnetic resonance (NMR), X-ray diffraction, mass spectrometry, and electronic spectroscopy in the UV-Vis region. The density functional theory (DFT density functional theory). The [Cu(phen-Bz-Sme)2(NO3)](NO3) complex was characterized by electronic spectroscopy in the UV-Vis and Infrared regions, in addition to electrochemical techniques such as cyclic voltammetry and surface plasmon resonance (SPR). Thus, it was possible to observe the ability of the complex ion [Cu(phen-Bz-Sme)2(NO3)]+ to adsorb onto the gold surface due to its sulfur ligands. Additionally, the DNA interaction experiments, monitored by electronic absorption spectroscopy, showed an association constant (Kb) of 8.73 x 105 mol L-1, with evidence of an intercalation process and interaction by the major groove of the DNA. The competition experiment between ethidium bromide (EB) and the complex ion demonstrated the intercalation capacity of the latter, presenting a Stern-Volmer constant of 4.2 x 104. Gel electrophoresis studies with plasmid pBR322 DNA demonstrated the capacity of the compound to cleave DNA through the generation of reactive oxygen species. In this way, it was concluded that it was possible to obtain a new copper complex capable of being adsorbed to the gold surface, in addition to cleaving DNA by oxidative pathways.